Finfish and shellfish bacteriology manual techniques and procedures. - Whitman, Kimberly A. (Ames, Iowa Iowa State Press, 2004)
with contributions by Neil G. MacNair
Keywords: Shellfish -- Microbiology -- Handbooks, manuals, etc; Fishes -- Microbiology -- Handbooks, manuals, etc